Public Health in the British Empire : intermediaries, subordinates, and the practice of public health, 1850-1960 - Johson,Ryan and Khalid,Amna Ed.; Johnson, Ryan; Khalid, Amna (New York : Routledge, 2012)
"Over the last several decades, historians of public health in Britain colonies have been primarily concerned with the process of policy making in the upper echelons of the medical and sanitary administrations. Yet it was the lower level staff that formed the backbone of public health systems in the colonies. Although they constituted the bases of many colonies public health machinery, there is no consolidated study of these individuals to date. Public Health in the British Empire addresses this gap by bringing together historians studying intermediary and subordinate staff across the British Empire.Along with investigating the duties and responsibilities of medical and non-medical intermediary and subordinate personnel, the contributors to this volume show how the subjectivity of these agents influenced the manner in which they discharged their duties and how this in turn shaped policy. Even those working as low level assistants and aids were able to affect policy design. In this way, Public Health in the British Empire brings into sharp relief the disaggregated nature of the empire, thereby challenging the understanding of the imperial project as an enterprise conceived of and driven from the center"--
Includes bibliographical references and index.
Keywords: Public health -- Great Britain; Public health -- Great Britain; HISTORY / Europe / Great Britain; HISTORY / Modern / 19th Century; HISTORY / Modern / 20th Century